Molecular dynamics investigation on the gasification of a coal particle in supercritical water. (7th February 2020) - Chen, Jian; Pan, Xiong; Li, Hanqing; Jin, Hanhui; Fan, Jianren
Abstract: Coal gasification technology in supercritical water provides a clean and efficient way to convert coal to H2 . In the present paper, the whole supercritical water（SWC）gasification process of a coal particle is studied with the reactive force field (ReaxFF) molecular dynamics (MD) method for the first time. First, the detailed reaction mechanism which can't be clearly illustrated in experiments, such as the evolution of the carbon structure during the gasification process and the detailed reaction mechanism of the main products, is obtained. According to the generation mechanism of H2, it is found that the supercritical water gasification process of a coal particle can be divided into two stages with different reaction mechanisms, namely the rapid reaction stage and the stable reaction stage. Then, the effects of temperature and coal concentration in the reaction system on the yield of H2 are studied. Finally, the transition of N in the coal particle is revealed, in which the precursors of NH3 such as CN, CHN, and CHON are the basic molecular structures for nitrogen atoms during the gasification process at high temperature. Highlights: The whole SCW gasification process of a coal particle is studied with ReaxFF. The carbon structure evolution and the generation mechanism of H2 are studied. The two stages of gasification process are disclosed. The temperature can significantly influence pyrolysis of the organic fragments. The transition of N in the coal particle is revealed.